A Systematic Review of the Pharmacology, Toxicology and Pharmacokinetics of Matrine - You, Longtai; Yang, Chunjing; Du, Yuanyuan; Wang, Wenping; Sun, Mingyi; Liu, Jing; Ma, Baorui; Pang, Linnuo; Zeng, Yawen; Zhang, Zhiqin; Dong, Xiaoxv; Yin, Xingbin; et al. (Frontiers in Pharmacology, 2020)
Matrine (MT) is a naturally occurring alkaloid and an active ingredient of Chinese herbs, including Sophora flavescens and Radix Sophorae tonkinensis. Emerging evidence suggests that anti-cancer, anti-inflammatory, anti-oxidant, antiviral, antimicrobial, anti-fibrosis, anti-allergic, antinociceptive, hepatoprotective, cardioprotective, and neuroprotective activities. These pharmacological properties lay the foundation for the treatment of various diseases, such as multiple types of cancers, hepatitis, skin diseases, allergic asthma, diabetic cardiomyopathy, analgesic, Alzheimer’s disease (AD), Parkinson's disease (PD), and central nervous system (CNS) inflammation. However, an increasing number of published studies indicated that MT has serious adverse effects, and the most obvious toxicity is liver toxicity and neurotoxicity, which has become the major factor limiting its clinical use and drug development. Pharmacokinetic studies have shown that MT has low oral bioavailability and short half-life in vivo. This review summarizes the latest advances in the research on the pharmacology, toxicology and pharmacokinetics of MT, with a focus on its biological properties and mechanism of action. This review provides insight into the future of traditional Chinese medicine research, which is important both historically and now.